Nietzsche and Jewish culture - Golomb, Jacob (Routledge, 1997)
This unique collection of essays explores the reciprocal relationship between Nietzsche and Jewish culture. It is organized in two parts: the first examines Nietzsche's attitudes towards Jews and Judaism: the second Nietzsche's influence on Jewish intellectuals as diverse and as famous as Franz Kafka, Martin Buber, Franz Rosenzweig and Sigmund Freud. Each carefully selected essay explores one aspect of Nietzsche's relation to Judaism and German intellectual history, from Heinrich Heine to Nazism.